Factors associated with knowledges and attitudes about measles and rubella immunization in a non-health care occupational setting in Japan. Issue 5 (May 2021) - Yahata, Yuichiro; Fielding, James E.; Kamiya, Hajime; Takimoto, Noriaki; Ishii, Jun; Fukusumi, Munehisa; Sunagawa, Tomimasa
Abstract: Introduction: Elimination of measles and rubella has been achieved in several countries and some regions. After verified measles elimination, some countries have reported outbreaks among adults in occupational settings such as health care institution and school setting. Studies have reported that knowledge and attitude for measles and/or rubella are significantly associated with immunization uptake in adults, but few studies have been conducted in settings other than health care facilities and schools. Methods: We conducted a cross-sectional study among 134 office employees during a routine health checkup in June 17–20, 2014, to examine the association between willingness to receive immunization and knowledge and attitudes. Results: Approximately 75% had a protective level of antibody for measles (PA≥1:256) and rubella (HI ≥ 32 IU/mL). After adjustment for sex, age and immune status, the attitudes that immunization prevents measles (adjusted odds ratio [aOR] = 7.8, 95% confidence interval [95%CI]: 2.5–24.7) and prevents infection and transmission to others (aOR = 4.0, 95%CI: 1.4–11.4). Knowing that males are the vulnerable group for rubella infection (aOR = 5.8, 95%CI: 2.4–13.9), attitude that immunization prevents rubella infection (aOR = 7.9, 95%CI: 2.4–26.5), and prevents infection and transmit to others (aOR = 6.7, 95%CI: 2.2–20.1) were significantly associated with willingness to receive immunization after adjustment for sex, age, and immune status. Conclusions: Studies have shown that physicians and other health care workers are important source of information for promotion of immunization. Thus, we recommend that physicians educate and promote immunization for measles and/or rubella to adults working in offices during routine health checks.